2020
DOI: 10.1111/tct.13242
|View full text |Cite
|
Sign up to set email alerts
|

How to … assess the quality of qualitative research

Abstract: SUMMARY As a clinician interested in qualitative research, you are likely to have pondered whether a particular study is trustworthy. How do you know whether qualitative research findings are valid and can be applied in your setting? The quality standards you would look for in quantitative research do not apply. Furthermore, qualitative research is conducted within a number of paradigms, or ways of understanding the nature of reality and knowledge, each associated with different ways of defining, understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 10 publications
0
87
0
Order By: Relevance
“…The inclusion of quotes or similar research data enhances the confirmability in the write-up of the findings. The use of expressions (for instance, ''80% of all respondents agreed that'' or ''only one of the interviewees mentioned that'') may also quantify qualitative findings (Stenfors et al, 2020). On the other hand, the persuasive reason for ''why this may not help in intensifying the research'' has also been provided (Monrouxe & Rees, 2020).…”
Section: Improving Quality: Strategiesmentioning
confidence: 99%
“…The inclusion of quotes or similar research data enhances the confirmability in the write-up of the findings. The use of expressions (for instance, ''80% of all respondents agreed that'' or ''only one of the interviewees mentioned that'') may also quantify qualitative findings (Stenfors et al, 2020). On the other hand, the persuasive reason for ''why this may not help in intensifying the research'' has also been provided (Monrouxe & Rees, 2020).…”
Section: Improving Quality: Strategiesmentioning
confidence: 99%
“…In order to improve the reliability of reviewers, one of the ways suggested by Kravitz et al [ 84 ] was providing more effective guidelines for reviewers, and one suggested by Kwon et al [ 85 ] was providing a checklist to reviewers. In more recent study, Stenfors et al [ 66 ] also suggested that guidelines may help to better identify criteria indicating high-quality research in journal publications. DiDomenico et al [ 86 ] discussed about previous studies that investigated the effectiveness of formal training on review quality and found the training to influence the review quality insignificantly or limitedly; thus, the authors suggested that reviewers may benefit from some guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Credibility of this study was enhanced through triangulation [ 38 , 39 ]. To achieve data triangulation, this study considered participants with experiences of research fellowship abroad in different countries and data collection was carried out at different times (i.e., after and during research fellowship abroad).…”
Section: Theoretical Frameworkmentioning
confidence: 99%